Odpowiedzi

2010-03-28T23:04:49+02:00
A) x² + x - 1 dla x = -1
(-1)² + (-1) - 1=1-1-1=-1

b) 2(-x + 4) dla x = -10
2(10+4)=2*14=28

c) 1 - y +x dla x = 2 i y = -1
1+1+2=4
19 4 19
2010-03-28T23:06:09+02:00
Oblicz wartość liczbową wyrażenia:
a) x² + x - 1 dla x = -1
1-1-1=-1
b) 2(-x + 4) dla x = -10
2(10+4)=2*14=28
c) 1 - y +x dla x = 2 i y = -1
1-(-1)+2=1+1+2=4
15 4 15
2010-03-28T23:06:50+02:00
A) x² + x - 1 dla x = -1
(-1)² + (-1) - 1 = 1 - 1 - 1 = - 1
b) 2(-x + 4) dla x = -10
2( - (-10) + 4 ) = 2 ( 10 + 4 ) = 20 + 8 = 28
c) 1 - y +x dla x = 2 i y = -1
1 - ( -1) + 2 = 1 + 1 + 2 = 4
11 4 11